Increasing diversity on public and private sector boards, Part 1 - How diverse are boards and why? - Sealy, Ruth; Doldor, Elena; Vinnicombe, Susan (Cranfield University, 2009)
The Government Equalities Office (GEO) commissioned Cranfield School of Management to examine the issue of diversity on boards of directors in the private and public sectors.The project sought to addresses two main questions: Why are there so few women and other under-represented groups on public and private sector boards? and What is being done in order to increase diversity on boards? The report is published in two parts: Part I considers the available evidence on diversity on boards. It examines academic and non-academic literature in the field, in the UK and internationally, and reviews available evidence concerning the factors accounting for the absence of diversity on boards. Part II maps out current practices aimed at increasing board diversity based.The review of evidence reviewed revealed a persistent under-representation of groups such as women, ethnic minorities and disabled people on both public and private sector boards. However, most evidence in the UK and internationally focused on gender rather than other underrepresented groups.